Dual Input Full Bridge Isolated DC to DC Converter. Issue 1 (August 2020) - Shimpi, Himani; Arunkumar, G.; Hunachal, Santoshkumar M.; Bhosale, Ajay; Kumar Jaysawal, Rajan
Abstract: This paper presents isolated dc to dc converter. It has dual input followed by two cascaded multilevel H bridge inverter and rectifier. This topology reduces the no of switches and components. Hence the cost of inverter is reduced and complexity is decreased. This is a major advantage over conventional topologies. This topology uses two DC sources which are asymmetrical, because of that seven level output voltage is obtain on the primary side of the transformer and step-up voltage obtain across the load. Switching techniques are used for proper working on this isolated converter and hence fulfil the objective of reducing overvoltage and stress in semiconductor devices. Simulation results are obtained in PSIM software.